Double-shell corrosion inhibition microsphere with slow release effect as well as preparation method and application of double-shell corrosion inhibition microsphere

By adopting the corrosion inhibitor microspheres with a bishell structure, using polyurea resin and melamine-formaldehyde resin as the inner and outer shell layers, the shortcomings of the existing corrosion inhibiting microspheres in terms of sustained release and sustained release performance are solved, and excellent encapsulation performance and continuous and stable sustained release effect are achieved, which is suitable for a variety of high-demand application fields.

CN120132734APending Publication Date: 2025-06-13SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510256944.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The existing corrosion-inhibiting microspheres have shortcomings in their sustained release effects and sustained release performance, and are difficult to meet certain high-demand application areas.

Method used

The corrosion inhibitor microspheres with a bishell structure are used. The inner shell layer is composed of polyurea resin and the outer shell layer is composed of melamine-formaldehyde resin. It is prepared by emulsification system and in-situ polymerization to achieve excellent encapsulation performance and continuous and stable sustained release effect.

Benefits of technology

It achieves excellent encapsulation performance and continuous and stable sustained release effect, and has excellent mechanical properties, which are suitable for coatings, cosmetics, functional materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005298630650000021
    Figure BDA0005298630650000021
  • Figure BDA0005298630650000051
    Figure BDA0005298630650000051
  • Figure BDA0005298630650000061
    Figure BDA0005298630650000061
Patent Text Reader

Abstract

The invention belongs to the technical field of corrosion inhibition materials, and discloses a double-shell corrosion inhibition microsphere with a slow release effect as well as a preparation method and application of the double-shell corrosion inhibition microsphere. The method comprises the following steps: 1) taking ethanol as a reaction medium, and reacting methionine with syringaldehyde under the action of a basic catalyst to obtain a core material; (2) mixing melamine and formaldehyde, adjusting the pH value to 7-10, stirring at 60-80 DEG C for 3-10 minutes, adding water, and continuously reacting for 30-50 minutes to obtain a melamine-formaldehyde prepolymer; (3) uniformly mixing the melamine-formaldehyde prepolymer with an emulsifier, adjusting the pH value to 1-6, adding a solvent, a curing agent and a core material, and emulsifying for 30-50 minutes under an ice bath condition; and heating, stirring, continuing the reaction, and adjusting the pH value to be greater than or equal to 6 to obtain the double-shell corrosion inhibition microspheres. The method is simple, and the prepared microspheres are good in corrosion inhibition effect, stable in quality and good in mechanical performance. The microspheres provided by the invention are used for cosmetics, adhesives and coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of corrosion - inhibiting microspheres, and particularly relates to a double - shell corrosion inhibitor microsphere with a sustained - release effect, its preparation method and application. Background Art

[0002] The microsphere technology, namely the micro - capsule technology, is a technology that encapsulates solid, liquid or gaseous substances within a tiny and enclosed capsule structure, aiming to achieve the controlled release of substances under specific conditions. Among them, the encapsulated substance is called the core material, and the substance responsible for forming the capsule shell and realizing micro - encapsulation is called the wall material. The types of core materials are numerous, covering oil - soluble, water - soluble compounds or mixtures, and their forms can be powders, solids, liquids or even gases. Specifically, cross - linkers, catalysts, chemical reaction agents, chromogenic agents, drugs, pesticides, aqueous solutions, dyes, pigments, detergents and foods, etc. can all be used as core materials. In the preparation process of micro - capsules, the selection of the outer wall material is also crucial. It is usually composed of natural polymers, semi - synthetic polymers or synthetic polymer materials, and is also called the capsule shell layer. To ensure the encapsulation effect and stability of micro - capsules, the properties of the wall material and the core material need to follow certain matching principles: generally speaking, oil - soluble core materials are preferably encapsulated with water - soluble wall materials, while water - soluble core materials are encapsulated with oil - soluble wall materials to avoid chemical reactions or miscibility between the wall material and the core material. The physicochemical properties of micro - capsules are closely related to the selected wall material. The characteristics of the wall material itself, such as permeability, stability, solubility, polymerizability, viscosity, electrical properties, hygroscopicity and film - forming properties, etc., will directly affect various properties of the shell layer. By encapsulating active core materials with inert wall materials, it is possible to effectively isolate the interference of external environmental factors (such as light, oxygen, water) on active substances, reduce the diffusion and evaporation of the core material into the environment, achieve precise control of the release rate of the core material, and at the same time mask the possible odors of the core material and change its physical properties, such as color, shape, density, dispersion properties and chemical properties, etc.

[0003] However, the existing corrosion - inhibiting microspheres need to be improved in terms of corrosion - inhibiting effect and sustained - release performance. Summary of the Invention

[0004] In order to overcome the shortcomings and deficiencies of the prior art, the purpose of the present invention is to provide a double - shell corrosion inhibitor microsphere and its preparation method. The corrosion inhibitor microsphere of the present invention uses an amino - acid - derivative corrosion inhibitor as the core material, and polyurea resin and melamine - formaldehyde resin as the inner and outer shell layers. The corrosion inhibitor microsphere of the present invention has excellent encapsulation performance and a continuous and stable sustained - release effect, and also has excellent mechanical properties.

[0005] Another purpose of the present invention is to provide the application of the corrosion inhibitor microsphere. This corrosion inhibitor microsphere is suitable for applications in coatings, cosmetics, functional materials and other fields, such as metal - protective coatings.

[0006] To achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0007] A preparation method of a double-shell corrosion inhibitor microsphere with a sustained-release effect, comprising the following steps:

[0008] 1) Preparation of the core material:

[0009] Using ethanol as the reaction medium, methionine and syringaldehyde are reacted under the action of an alkaline catalyst to obtain an amino acid derivative corrosion inhibitor, i.e., the core material; the alkaline catalyst is sodium hydroxide; the mass ratio of methionine to solid sodium hydroxide is 1:100 - 150; the dosage of syringaldehyde is 2 - 5 times the mass of methionine; the reaction temperature is 60 - 70 °C, and the reaction time is 2 - 3 hours; the reaction is carried out under stirring conditions; the stirring speed is 60 - 200 rpm;

[0010] 2) Mix 1 part by weight of melamine and 4 - 5 parts by weight of formaldehyde, adjust the pH to 7 - 10, stir at 60 - 80 °C for 3 - 10 min, add water, and continue to react for 30 - 50 min to obtain a melamine - formaldehyde prepolymer;

[0011] 3) Mix the melamine - formaldehyde prepolymer with an emulsifier, adjust the pH to 1 - 6, add a solvent, a curing agent, and an amino acid derivative corrosion inhibitor, and emulsify for 30 - 50 min under ice bath conditions; raise the temperature and stir to continue the reaction, adjust the pH ≥ 6 to obtain a double-shell corrosion inhibitor microsphere; the temperature of the temperature-raising stirring is ≥ 50 °C (such as: 50 - 70 °C); the emulsification speed is 500 - 2500 rpm; the stirring speed of the temperature-raising stirring is 50 - 400 rpm.

[0012] The double-shell corrosion inhibitor microsphere is made of the following components in parts by weight:

[0013]

[0014] The solvent is one or more of ethyl acetate, isobutyl acetate, methyl phenylacetate, bromobenzene, chlorobenzene, xylene, mesitylene, butyl acetate, ethyl phenylacetate;

[0015] The curing agent is an MDI prepolymer, an XDI prepolymer, a TDI prepolymer, or a TDI trimer, an IPDI trimer.

[0016] The emulsifier is sodium dodecyl sulfate.

[0017] The specific preparation method of the core material in step (1):

[0018] Mix methionine and sodium hydroxide with a mass ratio of 1:100 - 150 in 20 - 40 ml of absolute ethanol, stir and mix evenly at 60 - 70 °C, then add solid syringaldehyde with a mass 2 - 5 times that of methionine and ethanol with a mass 10 - 13 times that of methionine, stir and react for 2 - 3 hours, cool to room temperature, wash with absolute ethanol, centrifuge, and dry to obtain the amino acid derivative corrosion inhibitor SM. The drying conditions are drying at 50 - 60 °C for a drying time of ≥ 24 hours.

[0019] In step (2), formaldehyde is used in the form of a formaldehyde solution, and the volume concentration of the formaldehyde solution is 37%; the first pH regulator for adjusting the pH value to 7 - 10 is one or more of sulfuric acid, hydrochloric acid, benzoic acid, lactic acid, formic acid, succinic acid, oxalic acid, acetic acid, and citric acid.

[0020] In step (3), the rotation speed for mixing evenly is 60 - 100 rpm; the second pH regulator for adjusting the pH to 1 - 6 is one or more of magnesium hydroxide, barium hydroxide, potassium hydroxide, sodium hydroxide, lithium hydroxide, calcium hydroxide, triethylamine, trimethylamine, methylamine, ammonia water, and ethylenediamine.

[0021] The solvent, curing agent, and amino acid derivative corrosion inhibitor first form a homogeneous substance, and then emulsification is carried out.

[0022] The heating and stirring is turbine stirring, and the time for continuous reaction is 2 - 5 h.

[0023] Using polyurea resin and melamine - formaldehyde resin as the inner and outer double shells, the corrosion inhibitor microspheres can be used as additives for functional fine organic chemicals such as cosmetics, and the addition amount during use is 1 - 20% of the total mass. As a chemical additive, it can slowly release the active ingredient, which helps to extend the service life and shelf life.

[0024] Preferably, the addition amount during use is 5 - 10% of the total mass.

[0025] Using polyurea resin and melamine - formaldehyde resin as the inner and outer double shells, the corrosion inhibitor microspheres can be applied in the preparation of adhesives and coatings, and the addition amount during use is 1 - 30% of the total mass. When used in adhesives and coatings, the corrosion inhibitor microspheres help to provide long - term and environmentally - released anti - corrosion protection.

[0026] Preferably, the addition amount during use is 3 - 20% of the total mass.

[0027] The present invention relates to a corrosion inhibitor microsphere with an inner and outer double - shell structure. Its inner shell layer is composed of polyurea resin, and the outer shell layer is composed of melamine - formaldehyde resin. Such microspheres exhibit excellent encapsulation performance and continuous and stable slow - release effects, and at the same time have excellent mechanical properties, showing broad application prospects.

[0028] The principle of the present invention is as follows:

[0029] 1. In the emulsion system, the curing agent in the oil phase is dispersed into tiny droplets, and these droplets undergo an interfacial polymerization reaction with water molecules in the water phase and residual amines in the melamine-formaldehyde prepolymer, forming a polyurea resin inner shell layer. 2. Under acidic conditions, the melamine-formaldehyde prepolymer further condenses through in-situ polymerization and deposits on the surface of the already formed polyurea microspheres, ultimately forming corrosion inhibitor microspheres with a polyurea resin inner layer and a melamine-formaldehyde resin outer layer.

[0030] Compared with the prior art, the present invention has the following advantages:

[0031] 1) The green corrosion inhibitor amino acid derivative is adopted, and the corrosion inhibition efficiency and effect are more remarkable compared with existing corrosion inhibitor microspheres.

[0032] 2) The prepared corrosion inhibitor microspheres are white or off-white, with a uniform morphology, an average particle size between 0.1 - 300 μm; the moisture mass content does not exceed 5%; the critical stress is in the range of 0 - 900 mN, showing good mechanical properties.

[0033] 3) The prepared corrosion inhibitor microspheres not only control the slow release rate of the core material through the encapsulation of the inner shell layer, but also improve the impact resistance and chemical resistance of the microcapsules through the outer shell layer, ensuring the quality stability and storage stability of the product.

[0034] 4) The preparation method of the dual-core microcapsules is applicable to the encapsulation of various active substances, with a wide range of raw material sources and low prices for the shell layer raw materials.

[0035] 5) The preparation process is simple, and the produced dual-core microcapsules can be applied to multiple fields such as coatings, pharmaceuticals, and cosmetics, and can also be widely used in the field of functional materials, expanding the application scope of the microcapsules.

[0036] 6) In the preparation process, the residual formaldehyde content generated by the polycondensation reaction of melamine and formaldehyde is less than 5%, meeting the safety standards. The prepared corrosion inhibitor microspheres not only control the slow release rate of the core material through the encapsulation of the inner shell layer, but also improve the impact resistance and chemical resistance of the microcapsules through the outer shell layer, ensuring the quality stability and storage stability of the product. Description of the Drawings

[0037] Figure 1 Nuclear magnetic resonance diagram (a) and infrared spectrum diagram (b) of the amino acid derivative corrosion inhibitor SM prepared in Example 1;

[0038] Figure 2 Optical structure characterization diagram of the corrosion inhibitor microspheres prepared in Example 1;

[0039] Figure 3Infrared spectrum of corrosion inhibitor SM prepared as Comparative Example 1. Detailed implementation manners

[0040] The present invention will be further described in detail below in conjunction with specific embodiments, but the implementation manners of the present invention are not limited thereto.

[0041] Example 1

[0042] A corrosion inhibitor microsphere is made of components including the following parts by weight:

[0043]

[0044] A method for preparing a corrosion inhibitor microsphere with a polyurea resin and a melamine-formaldehyde resin as an inner and outer double shell layer includes the following steps:

[0045] (1) Preparation of the core material:

[0046] Dissolve methionine and solid sodium hydroxide with a mass ratio of 1:120 in 30 ml of absolute ethanol, place the mixed solution in a 60°C water bath and stir well; add solid syringaldehyde with 3 times the mass of methionine and ethanol with 12 times the mass of methionine, stir and react for 2.5 hours, cool to room temperature, wash and centrifuge 5 times with absolute ethanol, and dry at 60°C for 24 hours to obtain the amino acid derivative corrosion inhibitor SM, i.e., the core material.

[0047] (2) Preparation of the melamine-formaldehyde prepolymer:

[0048] Add melamine and 37% formaldehyde solution to the container in sequence according to the mass ratio of melamine to formaldehyde of 1:4.5, stir and mix, add hydrochloric acid to adjust the pH value of the system to 8; heat and stir the melamine-formaldehyde mixed solution in a 70°C water bath, and the system becomes transparent after 9 minutes, then add distilled water and continue to react for 45 minutes to obtain a transparent low molecular weight water-soluble melamine-formaldehyde prepolymer; the amount of water added to the system is 10 times that of melamine;

[0049] (3) Preparation of the melamine-formaldehyde resin microcapsule

[0050] Melamine-formaldehyde prepolymer and emulsifier sodium dodecyl sulfate (the mass ratio of melamine to emulsifier is 1:0.3) are added to a reactor, stirred at 80 rpm at room temperature until completely dissolved, the pH value is adjusted to 4 with aqueous ammonia, and then a homogeneous mixture of solvent ethyl acetate, curing agent MDI prepolymer (polyurethane prepolymer MDI) and the core material in step (1) is added (the mass ratio of melamine: solvent: curing agent: core material is 1:2:1.5:1), and emulsified at 1200 rpm and ice bath conditions for 35 minutes; then the water bath temperature is raised to 65°C, and a turbine stirrer is used to stir at 200 rpm. After continuing the reaction for 3 hours, the pH value is adjusted to 6.5.

[0051] The performance characterization method of the dual-core microcapsules prepared by the present invention is as follows: appearance test: observation and recording under natural light; average particle size: Malvern particle size analyzer; the amount of residual formaldehyde, measured by ultraviolet spectrophotometer; critical stress measured by microcontroller system (Model 403A); moisture measurement is performed in accordance with GB / T 6283-1986.

[0052] Figure 1 The NMR spectra (a) and IR spectra (b) of the hydroxyl acid derivative corrosion inhibitor SM prepared in this example are shown in FIG. SA is syringaldehyde and MTI is methionine.

[0053] Figure 2 This is a characterization diagram of the optical structure of the corrosion inhibitor microspheres (i.e., melamine-formaldehyde resin microcapsules) prepared in this example.

[0054] The corrosion inhibitor microspheres prepared in this embodiment have a residual formaldehyde content of less than 5%, an average particle size of 0.1-300 μm, a water content of no more than 5%, a critical stress of 0-900 mN, and an encapsulation rate of more than 86%.

[0055] Application Example 1

[0056] A water-based alkyd resin anticorrosive coating is prepared from the following components in parts by weight:

[0057]

[0058] Among them, the WX1008 is a product produced by Foshan Wanxia New Material Technology Co., Ltd. AEP selects products produced by BASF (China) Co., Ltd.

[0059] The acrylic acid anticorrosive coating is prepared by: AEP is dissolved in water, and WX1008, ammonia water and ethanol are added and dispersed at 1200r / min. When the amount of WX1008 is 100 parts by weight, The dosage of AEP is 4 parts by weight, the dosage of ethanol (EtOH) is 10 parts by weight, and the dosage of pure water is 50 parts by weight. When the pH of the solution is adjusted to 8 with ammonia water, it can be seen through detection that adding 9 parts by weight of the microcapsule corrosion inhibitor can increase the anti-corrosion ability of the cured product by 5%; adding 13 parts by weight of the microcapsule corrosion inhibitor can increase the light anti-corrosion ability of the cured product by 15%.

[0060] The slow-release performance of the corrosion inhibitor microspheres prepared in Example 1: The slow-release rate reaches 85% after 15 days (low dosage of microspheres).

[0061] Application Example 2

[0062] An epoxy anti-rust paint is made from the following components in parts by weight:

[0063]

[0064] The preparation method of the epoxy anti-rust paint is to mix and disperse the components according to the above formula. Through detection, adding 7 parts by weight of the microcapsule corrosion inhibitor can increase the anti-corrosion ability of the cured product by 10%; adding 13 parts by weight of the microcapsule corrosion inhibitor can increase the anti-corrosion ability of the cured product by 20%.

[0065] In this example, the corrosion inhibitor microspheres have a slow-release effect for 30 days.

[0066] Application Example 3

[0067] A polyurethane anti-rust paint is made from the following components in parts by weight:

[0068]

[0069] Among them, the polyether DL-3000D is a product produced by BlueStar Dongda Co., Ltd., and the polyether EP330NG is a product produced by BlueStar Dongda Co., Ltd.

[0070] The preparation method of the polyurethane rust-proof paint is to mix and stir 25 parts by weight of solvent, 50 parts by weight of polyether DL-3000D, 50 parts by weight of polyether EP330NG and 55 parts by weight of talc powder under the conditions of a temperature controlled at 90 °C and a rotation speed of 800 r / min for 30 minutes. Subsequently, the mixture is cooled to 75 °C, and 30 parts by weight of diphenylmethane diisocyanate is added, and stirring is continued for 30 minutes. Then, the reaction system is heated to 85 °C and maintained at this temperature for reaction until the total reaction time is 2.5 h. When the reaction is nearly complete, the system is cooled to 60 °C, and microencapsulated corrosion inhibitor powder is added, and 10 parts by weight of curing agent is added, and finally all components are uniformly mixed. It can be known from the detection that adding 5.3 parts by weight of microcapsule corrosion inhibitor can increase the anti-corrosion ability of the cured product by 20%; adding 10 parts by weight of microcapsule corrosion inhibitor can increase the anti-corrosion ability of the cured product by 35%.

[0071] In this example, the corrosion inhibitor microspheres have a sustained release effect of 35 days.

[0072] In the above application example, the anti-corrosion ability is tested electrochemically. In the three-electrode system for electrochemical testing, a platinum electrode is used as the auxiliary electrode, a saturated calomel electrode is used as the reference electrode, and Q235 carbon steel is used as the working electrode. The electrochemical testing medium is 3.5 wt% NaCl solution. The corrosion inhibition effect of adding corrosion inhibitor microspheres on Q235 carbon steel was evaluated by electrochemical impedance spectroscopy (EIS).

[0073] Corrosion inhibitor microsphere comparative example 1

[0074] In the preparation of the corrosion inhibitor SM, other conditions are the same as in Example 1, except that the stirring reaction time is shortened to 80% of the original. The infrared spectrum of the product of this comparative example is as Figure 3 shown.

[0075] It can be seen from the infrared characterization diagram that the image of the corrosion inhibitor product SM basically coincides with that of its raw material SA, and SM does not have characteristic peaks at 3000 cm -1 and 1670 cm -1 at two places, that is, functional groups with corrosion inhibition effects cannot be generated.

[0076] Corrosion inhibitor microsphere comparative example 2

[0077] In the double-shell coating step of the preparation process of the corrosion inhibitor microspheres, other conditions are the same as in Example 1, except that the mass ratio of melamine:solvent:curing agent:core material is 1:6:0.1:0.1, and when the pH value is finally adjusted to 5 in step (3), the corrosion inhibitor microspheres are analyzed and an experiment where a double shell cannot be formed.

[0078] Corrosion inhibitor microsphere comparative example 3

[0079] Replace methionine in Example 1 with leucine, and keep other conditions the same as in Example 1. The functional groups with corrosion inhibition effect cannot be generated, and the double-shell corrosion inhibition microspheres cannot be obtained.

Claims

1. A method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect, characterized in that: The following steps are involved: 1) Preparation of core material: Using ethanol as a reaction medium, methionine and syringaldehyde are reacted under the action of an alkaline catalyst to obtain an amino acid derivative corrosion inhibitor, namely a core material; the alkaline catalyst is sodium hydroxide; the mass ratio of methionine to solid sodium hydroxide is 1:100-150; the amount of syringaldehyde is 2-5 times the mass of methionine; the reaction temperature is 60-70°C, and the reaction time is 2-3 hours; 2) mixing 1 part by weight of melamine and 4-5 parts by weight of formaldehyde, adjusting the pH to 7-10, stirring at 60-80° C. for 3-10 minutes, adding water, and continuing the reaction for 30-50 minutes to obtain a melamine-formaldehyde prepolymer; 3) Mix the melamine-formaldehyde prepolymer and the emulsifier, adjust the pH to 1-6, add the solvent, curing agent and amino acid derivative corrosion inhibitor, and emulsify in an ice bath for 30-50 minutes; The reaction is continued with heating and stirring, and the pH is adjusted to ≥ 6 to obtain double-shell corrosion-inhibiting microspheres; the temperature of heating and stirring is ≥ 50° C.; the speed of emulsification is 500-2500 rpm; the speed of heating and stirring is 50-400 rpm; Double-shell corrosion inhibitor microspheres are made from the following components in parts by weight: The solvent is one or more of ethyl acetate, isobutyl acetate, methyl phenylacetate, bromobenzene, chlorobenzene, xylene, trimethylbenzene, butyl acetate, and ethyl phenylacetate; The curing agent is MDI prepolymer, XDI prepolymer, TDI prepolymer or TDI trimer, IPDI trimer.

2. The method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 1, characterized in that: The emulsifier is sodium lauryl sulfate.

3. The method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 1, characterized in that: Step 1) Specific preparation method of the core material: Methionine and sodium hydroxide in a mass ratio of 1:100-150 are placed in 20-40 ml of anhydrous ethanol, stirred and mixed at 60-70° C., and then 2-5 times the mass of methionine solid syringaldehyde and 10-13 times the mass of methionine ethanol are added, stirred and reacted for 2-3 hours, cooled to room temperature, washed with anhydrous ethanol, centrifuged, and dried to obtain an amino acid derivative corrosion inhibitor SM.

4. The method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 3, characterized in that: The drying condition is 50-60°C.

5. The method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 1, characterized in that: The reaction in step 1) is carried out under stirring; the stirring speed is 60-200 rpm; In step 2), formaldehyde is used in the form of formaldehyde solution, and the volume concentration of the formaldehyde solution is 37%; the first pH adjuster for adjusting the pH value to 7-10 is one or more of sulfuric acid, hydrochloric acid, benzoic acid, lactic acid, formic acid, succinic acid, oxalic acid, acetic acid, and citric acid.

6. The method for preparing double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 1, characterized in that: The mixing speed in step 3) is 60-100 rpm; the second pH adjusting agent for adjusting the pH to 1-6 is one or more of magnesium hydroxide, barium hydroxide, potassium hydroxide, sodium hydroxide, lithium hydroxide, calcium hydroxide, triethylamine, trimethylamine, methylamine, ammonia water, and ethylenediamine; In step 3), the solvent, curing agent and amino acid derivative corrosion inhibitor are first formed into a homogeneous phase and then emulsified; the heating and stirring is turbine stirring, and the reaction is continued for 2-5 hours.

7. A double-shell corrosion-inhibiting microsphere with sustained-release effect obtained by the preparation method according to any one of claims 1 to 6.

8. The use of the double-shell corrosion-inhibiting microspheres with sustained-release effect according to claim 7, characterized in that: The double-shell corrosion-inhibiting microspheres with sustained-release effect are used in cosmetics, adhesives and coatings.

9. The use according to claim 8, characterized in that: When used in cosmetics, the amount of the double-shell corrosion-inhibiting microspheres with sustained-release effect added is 1-20% of the total mass of the cosmetics; When used in adhesives and coatings, the added amount of the double-shell corrosion-inhibiting microspheres with slow-release effect is 1-30% of the total mass of the adhesive or coating.

10. The use according to claim 9, characterized in that: The added amount of the double-shell corrosion-inhibiting microspheres with sustained-release effect is 5-10% of the total weight of the cosmetics; The added amount of the double-shell corrosion-inhibiting microspheres with slow-release effect is 3-20% of the total mass of the adhesive or coating.